Kontroversi Komersialisasi Dakwah: Perspektif Dakwah Profetik - Muhammad Hamdan Yuwafik; Moh Muslimin; Afif Mahmudi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
The commercialization of da'wah is a growing phenomenon in the digital era, where preachers utilize social media platforms and offline events as sources of income. This study aims to analyze the controversy surrounding da'wah commercialization from the perspective of prophetic da'wah, which emphasizes humanization, liberation, and transcendence. Using a qualitative approach with a case study method, data was collected through interviews, observations, and documentation of preachers and the public. The findings indicate that while commercialization can expand the reach of religious messages, it also risks shifting da'wah into a profit-oriented activity. The study's implications highlight the need for clearer regulations and ethical guidelines to ensure alignment with prophetic values. This research contributes to understanding the balance between monetization and the essence of da'wah in the digital era.